Why should I share my knowledge? A multiple foci of commitment perspective. (25th February 2014) - Swart, Juani; Kinnie, Nicholas; van Rossenberg, Yvonne; Yalabik, Zeynep Y.
<x xml:space="preserve">Abstract</x> Knowledge‐intensive firms need to leverage their individual knowledge assets via knowledge sharing to create collective knowledge resources. This process is, however, in the control of the knowledge worker. We explore this personal and emotive quality of knowledge sharing by asking: 'How does employee commitment impact on knowledge sharing?' We study professional service firms operating in cross‐boundary environments and examine the impact of commitment to the organisation, profession, team and client on knowledge sharing. The article contributes directly to our understanding of the interrelationship between (a) the types and foci of commitment and (b) bidirectional knowledge sharing.